Inclusion and Repression of Animal Figures in the Short Fiction of Chekhov and Bangdel - Koirala, Saroj (Literary Studies, 2020)
Fiction is largely a domain of human beings having anthropocentrism as its organizing principle. However, the genre sometimes employs non-human animals too as characters which can be viewed as an innovative tool of modern narratology. Through the use of de-anthropomorphized characters such works provide space for an interpretation of animal behavior and their consciousness. Universally, human beings have kept companion pets as domestic animals are believed to be sentient beings compared to wild ones. For instance, archeological records of 15 millenniums have reported that dogs used to live together with humans because of their faithful companionship. Animals, therefore, abound in literature across all ages and cultures, but only rarely have they been the focal point of systematic literary study (McHugh 487). As a result, more recent literary criticism has focused on the ethics and the politics of human-animal bonds (HAB), animal communication, animal emotion and so on.